What is the answer to this question 3x+2y=11 2x+6y=-2
What is the answer to this question 3x+2y=11 2x+6y=-2
cake batter frozen yogurt costs $0.60/oz and chocolate frozen yogurt costs $0.40/oz. if you want to buy 6 oz of frozen yogurt for an average of $0.45/oz, how many of each flavor should you get
substituition
I have two questions that involve using either the elimination or substitution method and i need which method and how 1. 4x-7y=3 x-7y=-15 2. 3x+2y=-15...
The senior classes at High School A and High School B planned separate trips to Yellowstone National Park. the senior class at High School A rented and filled 13 vans and 11 buses with 647 students...
Explain, in complete sentences, how you would use the substitution method to solve the following system of equations. Provide the solution to the system. 2x - y = 5 x + 2y = 15
1) 7x+2y=-13, -3x-8y=-23 2) x-9y=-10, 6x+y=-5 3)x=y/4+1, y=4x-5 4)x-2y-1=0, y-5x+14=0 5) y=-8x-37, x+3y=4 6) 3x+6y=18, 3y...
1) suppose you got 8 mangoes and 3 apples for $18 and 3 mangoes and 5 apples for $14.50. How much does each mango and each apple cost? 2) Tia purchased 4 tables and 2 chairs for $200...
1) Jake purchased 8 t-shirts and 5 pairs of pants for $220. The next day, he purchased 5 t-shirts and 1 pair of pants for $112. How much does each t-shirt and each pair of pants cost? 2)Matt...
Solve each system by substitution. Check your solution. 1) x=y, x+2y=3 2) y= -x+4, y=3x 3) y=2x-10, 2y=x-8 4) 2y=x+1, -2x-y=7 5) x+2y=14, y=3x-15 6)2x-3y=13,...
I'm not getting it
Solve Y=5x-4y X+y=12 1/3x+y=1/2 X-y=3/4
Explain, in complete sentences, how you would use the substitution method to solve the following system of equations and provide the solution to the system. x + 5y = 3 2x + 9y...
The following system is solved by substitution. Which expression is substituted for z in the second and third equations? x + 4y + z = -10 3x - 3y + 6z = -21 x + 2y...
Solve y=x^2+7x+100 using substitution
how to use substitution method with these
0.4x+0.5y=0.2 0.3x-0.1y=1.1
show work please?
3x-y=5 y=4x+2 2x-y=1 5x-5y=10
lim cosθ-(1/√2)/(θ-π/4) θ→π/4 I rewrote θ as h so I have lim which is cosh-(1/√2)/h-(π/4) ...